2016
DOI: 10.3402/gha.v9.31744
|View full text |Cite
|
Sign up to set email alerts
|

Beyond ‘test and treat’ – malaria diagnosis for improved pediatric fever management in sub-Saharan Africa

Abstract: BackgroundMalaria rapid diagnostic tests (RDTs) have great potential to improve quality care and rational drug use in malaria-endemic settings although studies have shown common RDT non-compliance. Yet, evidence has largely been derived from limited hospital settings in few countries. This article reviews a PhD thesis that analyzed national surveys from multiple sub-Saharan African countries to generate large-scale evidence of malaria diagnosis practices and its determinants across different contexts.DesignA m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Evidence from literature suggests that clinicians show good adherence to integrated management of childhood illness (IMCI) guidelines when prescribing ACT after a positive RDT [19, 20], but information is sparse on clinicians’ propensity to investigate alternative causes of illness after either negative or positive RDT outcomes. Evidence suggests that in malaria-endemic areas, a shift from malaria-centric test-and-treat methods towards a holistic IMCI approach in clinics would both improve health outcomes and reduce unnecessary antibiotic use [21]. Studies have shown that clinicians are more likely to prescribe antibiotics to patients with a negative RDT than malaria-positive patients in a study in Zanzibar [20], and that after IMCI training clinicians do record diagnoses of malaria co-infections with NMFI [22].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from literature suggests that clinicians show good adherence to integrated management of childhood illness (IMCI) guidelines when prescribing ACT after a positive RDT [19, 20], but information is sparse on clinicians’ propensity to investigate alternative causes of illness after either negative or positive RDT outcomes. Evidence suggests that in malaria-endemic areas, a shift from malaria-centric test-and-treat methods towards a holistic IMCI approach in clinics would both improve health outcomes and reduce unnecessary antibiotic use [21]. Studies have shown that clinicians are more likely to prescribe antibiotics to patients with a negative RDT than malaria-positive patients in a study in Zanzibar [20], and that after IMCI training clinicians do record diagnoses of malaria co-infections with NMFI [22].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, primary healthcare workers often have low confidence in managing children with fever symptoms but negative tests for malaria. Recent studies show that mRDT-negative patients with cough or difficult breathing complaints in Malawi had 16.8 times higher odds of antibiotic overtreatment than mRDT-positive patients [ 41 ]; in Burkina Faso and Uganda both community and health facility workers prescribed antimalarials to mRDT-negative patients if no other fever cause was identified, often due to parental pressure [ 41 , 42 ]. However, when clear case management instructions were provided, as in this study, and non-malaria fever was introduced as a diagnostic term, HEWs felt empowered to withhold medicines, while simultaneously reassuring caregivers that their child was cared for [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…19,20 In addition, although since 2010 the recommendation has been that antimalarial medication should only be given when a case is confirmed positive, 21 health workers still experience mistrust in mRDTs and insecurities about managing febrile children with negative mRDT results, thus often resorting to the use of antimalarials even when unnecessary. [22][23][24][25] It has been described that showing the test result to patients can help increase patients' trust and that a lack of communication about the test can lead to a patient misinterpreting its result. 20 Thus, particularly for negative malaria test results and low fever, where according to iCCM no medication should be given, clear communication to caregivers of sick children becomes important.…”
Section: Discussionmentioning
confidence: 99%